In Silico Analysis of Physical-Chemical Properties, Target Potential, and Toxicology of Pure Compounds from Natural Products - Purnawan Pontana Putra; Annisa Fauzana; Henny Lucida (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Several studies have shown that pure compounds from west sumatera medicinal plants have beneficial therapeutic effects so that they are potential candidates for active pharmaceutical ingredients (API). Andalas Sitawa Fitolab has been able to produce 10 pure isolates. The development of a new drug candidate requires an in silico study to predict physicochemical properties, potential target, and toxic properties. The purpose of this study was to initially screen the structure of candidates to predict the potential the compound as an API by using big data and machine learning. The chemical structure were analyzed using software and servers. The Software used was Marvin Sketch, QSAR Toolbox, Swiss Potential Target and ChemBioDraw. Results showed that log P of compounds revealed in a range of -0.54 to 4.64, Polar Surface Area (PSA) in range of 20.23 to 315.21. Asiaticoside did not meet Lipinski's rules. Compounds with high potential hazard were catechin, curcumin, andrographolide, asiaticoside deoxyelephantopin, ethylmethoxycinnamate, alpha-mangostin and piperine. The compounds such as curcumin, alpha mangostin, plumbagin, and piperine were predicted to have spesific target proteins. This study concluded that asiaticoside compounds have a high potential hazard, if it was developed as an API.Keywords: analysis of physical-chemical properties, in silico, pure isolate, toxicology